2001
DOI: 10.1128/mcb.21.7.2449-2462.2001
|View full text |Cite
|
Sign up to set email alerts
|

The Cbk1p Pathway Is Important for Polarized Cell Growth and Cell Separation in Saccharomyces cerevisiae

Abstract: During the early stages of budding, cell wall remodeling and polarized secretion are concentrated at the bud tip (apical growth). The CBK1 gene, encoding a putative serine/threonine protein kinase, was identified in a screen designed to isolate mutations that affect apical growth. Analysis of cbk1⌬ cells reveals that Cbk1p is required for efficient apical growth, proper mating projection morphology, bipolar bud site selection in diploid cells, and cell separation. Epitope-tagged Cbk1p localizes to both sides o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
281
0
11

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(307 citation statements)
references
References 60 publications
15
281
0
11
Order By: Relevance
“…The defects of pag1-1 cells in cell separation, cell shape, and mating projection formation were similar to the known defects of cbk1⌬ mutants (Racki et al, 2000;Bidlingmaier et al, 2001). This similarity led us to hypothesize that PAG1 and CBK1 may have related functions.…”
Section: A Pag1 Mutant Displays Morphogenesis Defects Similar To Thossupporting
confidence: 52%
See 4 more Smart Citations
“…The defects of pag1-1 cells in cell separation, cell shape, and mating projection formation were similar to the known defects of cbk1⌬ mutants (Racki et al, 2000;Bidlingmaier et al, 2001). This similarity led us to hypothesize that PAG1 and CBK1 may have related functions.…”
Section: A Pag1 Mutant Displays Morphogenesis Defects Similar To Thossupporting
confidence: 52%
“…Previous studies found that cbk1⌬ had no growth defect (Racki et al, 2000;Bidlingmaier et al, 2001). However, we showed that CBK1 is essential for cell proliferation in a standard yeast strain and that the lethality of cbk1⌬ can be suppressed by disruption of the SSD1 gene.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations